Detection of the Largest Deep-Sea-Endemic Teleost Fish at Depths of Over 2,000 m Through a Combination of eDNA Metabarcoding and Baited Camera Observations - Fujiwara, Yoshihiro; Tsuchida, Shinji; Kawato, Masaru; Masuda, Kotohiro; Sakaguchi, Sakiko Orui; Sado, Tetsuya; Miya, Masaki; Yoshida, Takao (Frontiers in Marine Science, 2022)
The Yokozuna Slickhead Narcetes shonanmaruae is a recently described deep-sea fish species and an active-swimming, relatively large top predator in Suruga Bay, Japan. Its only known habitat is the deepest part of the bay (>2,000 m); six individuals have been collected thus far (up to 138 cm in total length). During our monitoring survey of faunal diversity on seamounts within marine protected areas in Japanese waters, environmental DNA (eDNA) metabarcoding revealed the Yokozuna Slickhead 12S ribosomal RNA gene sequence on/around three seamounts belonging to the Nishi-Shichito Ridge (at depths of around 2,000 m) located 400–600 km south of the known locality. A baited camera system deployed at the foot of one of the three seamounts at a depth of 2,091 m captured a Yokozuna Slickhead individual that was over 250 cm in total length, threatening Pacific Grenadiers Coryphaenoides acrolepis around the bait and attacking the bait cage. A combination of eDNA metabarcoding and baited camera observation represents a powerful tool for the detection of rare predatory fish species and the study of their ecology even in the deep sea, thus helping to better understand vulnerable marine ecosystems and reveal the impact of the rapidly changing global ocean.